On taxation, political accountability and foreign aid: empirics to a celebrated literature - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
The Eubank (2012, JDS) findings on taxation, political accountability and foreign aid has had an important influence in academic and policy-making debates. Eubank has warned that his findings should not be generalized across Africa until they are backed by robust empirical evidence. This paper puts some empirical structure to the celebrated literature. The empirical evidence which is based on data from 53 African countries for the period 1996-2010 broadly confirms the Somaliland-based Eubank (2012) hypothesis that in the absence of foreign aid, the dependence of government on local tax revenues provides the leverage for better political governance.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Political Economy; Development; Africa